1991
DOI: 10.1128/jb.173.21.6732-6741.1991
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Butyrivibrio fibrisolvens glgB gene, which encodes a glycogen-branching enzyme with starch-clearing activity

Abstract: (calculated Mr, 73,875) with 46 to 50% sequence homology with other branching enzymes. A limited region of 12 amino acids showed sequence similarity to amylases and glucanotransferases. The B. fibrisolvens branching enzyme was not able to hydrolyze starch but stimulated phosphorylase a-mediated incorporation of glucose into a-1,4-glucan polymer 13.4-fold. The branching enzyme was purified to homogeneity by a simple two-step procedure; N-terminal sequence and amino acid composition determinations confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Significant similarity was also noted between spoVJ of Bacillus subtilis (5) and a partial sequence of a gene adjacent to glgB in Butyrivibrio fibrisolvens (28). Alignment of the deduced amino acid sequences revealed several regions of invariant residues among the CbbX-like sequences, including a putative ATP binding site situated at position 75 in the R. sphaeroides sequence (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Significant similarity was also noted between spoVJ of Bacillus subtilis (5) and a partial sequence of a gene adjacent to glgB in Butyrivibrio fibrisolvens (28). Alignment of the deduced amino acid sequences revealed several regions of invariant residues among the CbbX-like sequences, including a putative ATP binding site situated at position 75 in the R. sphaeroides sequence (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Although the function is not known, cbbX shows a rather broad distribution in CBB cycle gene clusters, insofar as a related sequence has been identified downstream from a chloroplast RubisCO coding sequence in a red alga (18) in addition to its presence in chemoautotrophic bacterial gene clusters (19,23). Interestingly, cbbX also has considerable sequence similarity with genes in unrelated systems, e.g., spoVJ, which is involved in some unknown way in sporulation in B. subtilis (5), and a gene adjacent to a glycogen-branching enzyme gene cluster in Butyrovibrio fibrisolvens (28). Although the functions of the gene products in these two systems are unknown, a role specific to CBB cycle function can reasonably be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Our main interest is focused on the bacterial branching Received 23 July, 1993; enzyme, which catalyses the fom^ation of the a-1,6glucosidic linkages in glyccgen by scission of a 1,4-c£linked oligosaccharide from growing c(-1,4-glucan chains and the subsequent transfer of the oligosaccharide to other parts of :i-1,4-glucan chains. A number of bacterial branching enzyme genes have recently been characterized (Baecker etal., 1986;Kiel etal., 1990;Rumbak et al, 1991). In Escherichia coli genes involved in glycogen metabolism are clustered on the bacterial chromosome in two operons (Preiss and Romeo, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…GH13_9) and the carbohydrate binding module CBM48. Both these modules have been shown to be involved in starch degradation 45,46 , and our metaproteome further suggested that these two MAGs also expressed several enzymes involved in fermentation of starch-derived sugars (i.e. glycolysis, Figure 4).…”
Section: Metaproteome-generated Cazyme Profile Indicates Compartmentamentioning
confidence: 68%